Teachers' practices and mental models: Transformation through reflection on action - Manrique, Maria Soledad (2015)
This contribution explores the relationship between teaching practices, teaching discourses and teachers' implicit representations and mental models and the way these dimensions change through teacher education (T.E). In order to study these relationships, and based on the assumptions that representations underlie teaching practices and that T.E might affect these representations, a T.E course was designed and implemented in Argentina. The course focused on teacher intervention in personal narrative telling in kindergarten. It was based on a reflection-onaction process. The personal narrative activities of 10 in-service teachers before and after the course were analysed employing the Process of Constant Comparison (Glaser & Straus, 1967). A case study was then conducted in order to infer possible transformations in one of the teachers' implicit representations and mental models, through Content Analysis (Krippendorf, 1990) of in-depth interviews before, during and after the course.